Determinanty vzniku kardiovaskulárních onemocnění v české populaci - Lustigová, Michala (Zdraví - výzvy a rizika, 2013)
Determinants of cardiovascular diseases are well known; nowadays more than 300 of CVD risk factors are well-established. Important factors from population approach (public health approach) point of view are those which meet following criteria: high prevalence in population, are preventable and their control results in reducing of CVD risk. Survival analysis using the HAPIEE cohort data was applied to set down determinants of fatal cardiovascular events among Czech middle-aged population. High prevalence of several CVD risk factors was found. Favourable findings for all major risk factors, corresponding to low CVD risk, were uncovered just only in 0.5 % of population. The impact of education on CVD mortality was confirmed from socioeconomic determinants; from major risk factors the impact of smoking, high blood pressure and physical inactivity was establish. Conversely the influence of obesity, binge drinking habits and high total cholesterol was not significant. Joint influence of several risk factors increased the CVD risk and favourable findings for risk factors significantly decreased the CVD risk.
Keywords: dospělí; Statistics as Topic; Female; statistika jako téma; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Aged, 80 and over; Risk Factors; Male; Cardiovascular Diseases; Aged; Czech Republic; Young Adult; rizikové faktory; kardiovaskulární nemoci; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; mladiství; Humans